2020
DOI: 10.1186/s12903-020-01313-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of early angiogenesis indicators in mature versus immature teeth

Abstract: Background Proper oxygen balance in the dental pulp is essential for cell metabolism. Angiogenesis in the pulp is a constant process during the life of the tooth. Hypoxia indicators in a tissue, such as HIF-1α, as well as vascular destabilization markers, such as ANG2 and its receptor TIE2, are necessary for angiogenesis. Therefore the purpose of this study is to evaluate the expression of HIF-1α, ANG1, ANG2 and TIE2 in dental pulp as early angiogenesis indicators in teeth with complete and incomplete root dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Similar results were found in equal dental groups with the same root characteristics: immature teeth with apical foramen greater than 5mm (16-19 years) and mature teeth with apical foramen not greater than 0.5mm (17-29 years). In which it was observed that HIF-1a, ANG1, ANG2 and TIE2 were significantly higher in mature teeth than in mature ones, showing that other proteins with angiogenic potential follow the same trend as the present investigation ( 25 ).…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were found in equal dental groups with the same root characteristics: immature teeth with apical foramen greater than 5mm (16-19 years) and mature teeth with apical foramen not greater than 0.5mm (17-29 years). In which it was observed that HIF-1a, ANG1, ANG2 and TIE2 were significantly higher in mature teeth than in mature ones, showing that other proteins with angiogenic potential follow the same trend as the present investigation ( 25 ).…”
Section: Discussionsupporting
confidence: 85%